Fungal Diagnostics Methods and Protocols - O'Connor, Louise; Glynn, Barry; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Invasive fungal infections are a significant cause of morbidity and mortality. Over the past decade there has been a concerted effort to develop reliable methods for the detection of such infections. In Fungal Diagnostics: Methods and Protocols, expert researchers in the field detail method performance, ease of use and turnaround time of innovative diagnostic methods. Focusing mainly on fungal detection in clinical settings, the methods described could also be applied to alternative fields such as environmental testing, agriculture, food production and veterinary diagnostics. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, Fungal Diagnostics: Methods and Protocols seeks to aid scientists into the further study of fungal detection.
Keywords: Microbiology; Microbiology